ChemInform Abstract: Organocatalytic Asymmetric Synthesis of Dihydrobenzoxazinones Bearing Trifluoromethylated Quaternary Stereocenters. Issue 29 (29th June 2016) - Lou, Hengqiao; Wang, Yongtao; Jin, Enze; Lin, Xufeng
Abstract: A chiral phosphoric acid‐catalyzed enantioselective aza‐Friedel—Crafts reaction of trifluoromethyl benzoxazinones with pyrroles is given.